MODIFIKASI DIGITAL ELEVATION MODEL (DEM) CITRA RESOLUSI TINGGI MENGGUNAKAN FUSI INTERFEROMETRI SAR DAN STEREOSAR BERBASIS FAKTOR PEMBOBOTAN - Dyatmika, Haris S.; Arief, Rahmat; Sudiana, Dodi; Ali, Shadiq; Maulana, Rachmat; Budiono, Marendra Eko (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
SAR satellite sensors are capable to measure elevation of the earth surface using interferometry (InSAR) or radargrammetry (StereoSAR) methods. The InSAR method utilizes phase value from SAR images, while the StereoSAR uses amplitude value to produce elevation of the earth surface. Both methods have advantages and disadvantages on each own. Problems with low accuracy on DEM generated using InSAR occur on shadow and layover area, while in the second method (StereoSAR) the problem arise when cross correlation between the two images have low value. This paper proposes a technique to combine InSAR and StereoSAR methods to generate DEM using high resolution SAR images. A pair of TerraSAR-X or TanDEM-X images with a 21 degree incidence angle are used in this study and processed using the InSAR method and another pair of images at an angle of 21 degrees and 41 degrees using the StereoSAR method in Bandung and surrounding areas. The experimental results show that the fusion DEM of the two methods have better accuracy and decrease the absolute error both from InSAR and StereoSAR technique methods that separately around 3.48 m and 1.80 m.